Calvin - Saint or Sinner? - Selderhuis, Herman J. (Mohr Siebeck, 2010)
The Calvin year 2009 began on October 31, 2008 with a conference organized by the Institute for Reformation Research (Apeldoorn) on the topic »Calvin: Saint or Sinner?« A number of scholars dealt with the question of whether and how Calvin brought a renewal to theology, the church and society. This volume contains the papers held at this conference, which demonstrate the detailed and growing research on the reformer of Geneva. Since the contributions reflect the latest research in Calvin studies, the conclusions reached in many of the papers are surprising. Calvin was not a reformer in all respects in the original sense, as some would have wanted him to be. However on other subjects he definitely distanced himself from tradition and from his fellow reformers. All in all, this volume gives an overview of the many facets of John Calvin and his theology.